Synthesis and excited state processes of arrays containing amine-rich carbon dots and unsymmetrical rylene diimides - Dordevic, Luka (2020)
Combining carbon dots (CDs) with p-extended chromophores is an attractive way to study the electronic and energy processes of the former as a key step to many applications, including photosensing, photocatalysis, or photosensitization. CDs, in conjugation with chromophores, can have value in preparing donor–acceptor hybrids, and can also be used as scaffolds to support electronic communication between dyes. In this work, we conjugate two different rylene diimides, naphthalene and perylene diimides (NDI and PDI, respectively), with amorphous nitrogen-doped carbon dots. We take advantage of the imidization reaction between the amine-rich surface of the carbon dots and the monimide monoanhydride precursors of NDIs and PDIs, under microwave assisted conditions. The resulting (nano)hybrids were characterized also by spectroscopic methods. In particular, time-resolved spectroscopy for the multichromophoric array, consisting of CDs and both rylene diimides, allowed us to elucidate the complex inter-chromophoric interactions taking place in the excited state.